Enzymatic destruction of protopectin in vegetable raw materials to increase its structuring ability in ice cream - Sapiga, Victoria; Polishchuk, Galyna; Breus, Natalia; Osmak (Fedchenko), Tetiana (My University, 2021)
The expediency of protopectin enzymatic hydrolysis of vegetable raw materials as a functional-technological semi-finished product for ice cream production is proved. In dispersed food systems, pectins as protective colloids have a stabilizing and emulsifying ability, form a creamy consistency, increase whipping and control syneresis, which is important for the formation of ice cream quality indicators. Highly purified pectin preparations are usually used in ice cream.
Keywords: ice-cream; vegetable; pectin; морозиво; овочі; пектин; кафедра технології молока і молочних продуктів; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки